2013
DOI: 10.1039/c2cp42810e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide at the air–water interface: trapping, absorption, and solvation in the bulk and at the surface

Abstract: The interaction of NO(2) with water surfaces in the troposphere is of major interest in atmospheric chemistry. We examined an initial step in this process, the uptake of NO(2) by water through the use of molecular dynamics simulations. An NO(2)-H(2)O intermolecular potential was obtained by fitting to high-level ab initio calculations. We determined the binding of NO(2)-H(2)O to be about two times stronger than that previously calculated. From scattering simulations of an NO(2) molecule interacting with a wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
(79 reference statements)
6
37
0
Order By: Relevance
“…A recent theoretical study 2 of the interaction of nitrogen dioxide with the surface of water led to the conclusion that, even though the binding energy of the O 2 N-OH 2 complex was found to be 9.5 kJ mol −1 , a factor of 2 larger than previously calculated, nitrogen dioxide is at least "mildly" hydrophobic. Instead of taking part in hydrogen bonds, the oxygen atoms of NO 2 were found to be repelled by water molecules, which led to an unexpected preferential orientation of NO 2 at the surface, with the oxygen atoms pointing out of the interface, and suggested that, in a system with mixed solvents, the surface might actually be depleted of water.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent theoretical study 2 of the interaction of nitrogen dioxide with the surface of water led to the conclusion that, even though the binding energy of the O 2 N-OH 2 complex was found to be 9.5 kJ mol −1 , a factor of 2 larger than previously calculated, nitrogen dioxide is at least "mildly" hydrophobic. Instead of taking part in hydrogen bonds, the oxygen atoms of NO 2 were found to be repelled by water molecules, which led to an unexpected preferential orientation of NO 2 at the surface, with the oxygen atoms pointing out of the interface, and suggested that, in a system with mixed solvents, the surface might actually be depleted of water.…”
Section: Introductionmentioning
confidence: 88%
“…Kolb et al 1 have presented a thorough review, up to 2010, of outstanding theoretical and experimental problems relating to the reactions of atmospheric trace gases, including NO 2 , with a variety of wet and dry surfaces, and it is clear that there are still many interesting problems that need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between the runs, the systems were again equilibrated in constant volume simulation and constant target temperature. The condensation probability, , was computed as = , where was the total number of adsorbed and absorbed octane molecules, and included all adsorbed, absorbed, scattered, and desorbed octane molecules [164,184]. Five bulk temperatures, 290 K, 300 K, 310 K, 330 K, and 350 K, were considered to explore the range of existing experimental setup [185] and to extend the range of available literature data [161].…”
Section: Molecular Dynamics Simulation Setupmentioning
confidence: 99%
“…Since at equilibrium, the evaporation and condensation coefficients are the same, throughout this work, mass accommodation and condensation coefficient are used interchangeably. The mass uptake and interactions at the liquid-gas interfaces are important and studied in other areas including physics of atmospheric aerosols [162][163][164].…”
Section: Introductionmentioning
confidence: 99%